Health Disparities in a Diverse County: Investigating Interactions between Residents and Neighborhoods - Barile, John P (2010)
This study evaluated the associations of individual and neighborhood level risk factors with physical health, mental health, and stress in a diverse urban county. Relatively little research has attempted to disentangle the interactive individual characteristics and neighborhood conditions underlying health outcomes and disparities. To address this, survey data were collected and analyzed from 1,107 residents living in one of the 114 census tracts in DeKalb County, GA. Using multilevel structural equation modeling techniques, this study found that neighborhood level measures of the social and built environment were not associated with the health outcomes under study after controlling for neighborhood level income and education. Alternatively, individual level perceptions of the social and built environment and measures of access to health care were significantly associated with physical health, mental health, and perceived stress. This study also found that the association between low individual income and poor physical health was more pronounced for participants who lived in low-income neighborhoods than participants who lived in high-income neighborhoods. Additionally, this study found that Black residents reported significantly better mental health compared to White residents when they lived in high-income neighborhoods, and Black participants reported significantly more stress compared to White participants when they lived in low-income neighborhoods. Results of this study further scientific understanding of the role of neighborhood processes in health disparities and potentially help inform the development of programs and policies related to neighborhood conditions and health disparities